CUSTOMER RELATIONSHIP MANAGEMENT STRATEGY TO RETAIN CUSTOMERS IN WHOLESALE MUSLIM WEBSITE BASED - Dyah Anisah; Novica Irawati; Iin Almeina Lubis (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: Along with the very rapid development of technology, there are many shops and business entities whose sales systems use the latest technology, nowadays if companies use the internet in their information systems or online sales, they get new customers and the convenience of customers in accessing the products offered. Muslim wholesalers must understand the desires of their customers in increasing customer satisfaction in maintaining good relations between customers and business owners. Customer Relationship Management (CRM) is one of the right ways to pay attention to customers at Guntur Jaya Stores in order to create communication links with their customers. CRM can also help Muslim wholesale stores with what customers need related to fashion products. The results of research conducted on Muslim wholesale stores can help in increasing customer loyalty, maintaining good relationships with customers. Furthermore, it will make it easier for Muslim wholesale stores to sell fashion products that are in accordance with the wishes of their            Keywords: Customer Relationship Management (CRM); Customer; Information System  Abstrak: Seiring dengan perkembangan teknologi yang sangat pesat, banyak sekali toko- toko maupun badan usaha yang memperbarui sistem penjualan dengan menggunakan teknologi terbaru, dewasa ini jika perusahaan menggunakan internet dalam sistem informasinya ataupun penjualannya secara online mendapatkan pelanggan baru dan kemudahan kepada pelanggan dalam mengakses produk yang ditawarkan.  Grosir Muslim harus bisa memahami keinginan pelanggannya dalam meningkatkan kepuasaan pelanggan dalam menjaga hubungan baik antara pelanggan dan pemilik usaha. Customer Relationship Management (CRM) merupakan salah satu cara yang tepat untuk memperhatikan pelanggan pada Toko Guntur jaya agar terciptanya jalinan komunikasi dengan para pelanggannya. CRM juga dapat membantu toko grosir muslim apa saja yang dibutuhkan para pelanggan terkait dengan produk fashion. Hasil dari penelitian yang dilakukan pada toko grosis muslim dapat membantu dalam meningkatkan loyalitas pelanggan, menjaga hubungan baik dengan pelanggan. Selanjutnya akan memudahkan toko grosir muslim dalam penjualan produk fashion yang sesuai dengan keinginan para pelanggan. Kata kunci: Customer Relationship Management (CRM); Konsumen; Sistem Informasi